Leadership education in professional and graduate schools. Issue 171 (18th October 2021) - Simen, Janice Hoffman; Meyer, Tina
Abstract: This article makes a case for the need of graduate leadership curricula, including professional programs such as health care, law, and engineering. Diversity, equity, and inclusion is focused on as a critical piece of this leadership curricula.